Determination of Interest in Purchasing Scarlett Whitening Products on the Shopee Marketplace - Lia Eka Sari; Nafik Umurul Hadi (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This study aims to determine the influence of celebrity endorsers andthe brand image on the interest in purchasing Scarlett Whitening products for EconomicEducation students at Bhinneka PGRI University in the Shopee marketplace.Design/Methodology/Approach – The method used in this research is descriptivequantitative with analysis using Partial Least Square (PLS). This study uses primarydata sources derived from questionnaires related to celebrity endorsers, brandimage, and purchase intention. This study determines the target population, namelythe Economic Education students of Bhinneka PGRI University, prospectiveconsumers, and consumers of Scarlett Whitening Products totaling 364 students witha sample of 91 students.Findings – The results showed that (1) Celebrity endorser (X1) has no significanteffect on purchase intention (Y) on Scarlett Whitening products, the P-Values valueis 0.203> 0.05 so that H1 is rejected; (2) Brand image has a positive and significanteffect on purchase intention (Y) on Scarlett Whitening products with a P-Valuesvalue of 0.000 <0.05, so H2 is accepted; (3) Celebrity endorser and brand imagesimultaneously do not affect purchase intention (Y) for Scarlett Whitening products